Methylomic Changes of Autophagy-Related Genes by Legionella Effector Lpg2936 in Infected Macrophages - Abd El Maksoud, Ahmed I.; Elebeedy, Dalia; Abass, Nasser H.; Awad, Ahmed M.; Nasr, Ghada M.; Roshdy, Tamer; Khalil, Hany (Frontiers in Cell and Developmental Biology, 2020)
Legionella pneumophila is a Gram-negative bacteria that infects human respiratory tract causing Legionaries disease; a severe form of pneumonia. Recently, rising evidence indicated the ability of Legionella to regulate host defense via its type 4 secretion system including hundreds effectors which promote intracellular bacterial replication. Host defense against such invaders includes the autophagic machinery which is responsible for degradation events of invading pathogens and recycling of cell-components. The interplay between host autophagy and Legionella infection has been reported indicating the role of bacterial effectors in regulation of autophagy during intracellular replication. Here we investigated the potential impact of Legionella effector Lpg2936 in regulation of host autophagy and its role in bacterial replication using mice-derived macrophages and human lung epithelial cells (A549 cells). First, monitoring of autophagic flux following infection revealed marked reduction of LC3B and Atg7 expression profile and low accumulation levels of autophagy related LC3II protein and Atg5-Atg12 protein complex. Second, analyzing the methylation changes in promoter regions of Atg7 and LC3 showed irreversible changes of GATC motif to G(6mA)TC, a novel methyladenine change, indicated by cleaved fragments with DpnI-dependent N6-methylAdenine. Interestingly, blocking of Lpg2936 in infected microphages by RNAi showed dramatic inhibition of bacterial replication through restoring the expression of autophagy related proteins. This is accompanied with low production levels of bacterial-associated pro-inflammatory cytokines. Furthermore, a constructed Lpg2936 segment in GFP expression vector was translocated in host nucleus and successfully regulated autophagic machinery in A549 cells independent from infection. Finally, treatment with methylation inhibitors, 5-AZA and (2)-Epigallocatechin-3-gallate (EGCG) was able to restore autophagy related genes expression and to disrupt bacterial replication in infected macrophages. Collectively, these data provide cumulative evidence indicating the methylation activity of Legionella effector Lpg2936 on host autophagy related molecules Atg7 and LC3B that resulted in low production levels of autophagy effectors during intracellular replication of L. pneumophila.